A Data-Driven Response to the Addiction Crisis in Hamilton County, Ohio. Issue 6 (November 2022) - Manchak, Sarah M.; Gosney, Meagan E.; Haberman, Cory; Firesheets, Kelly C.
Abstract : Context: For more than a decade, the state of Ohio has been an epicenter of the opioid crisis. Multiple interventions have been deployed to address this crisis and reduce opioid overdoses and overdose deaths in the state. The Hamilton County Addiction Response Coalition (HC ARC) and its strategic, countywide prearrest diversion (LEAD) and deflection (QRT) programs have been at the forefront of this effort in Cincinnati, Ohio. Operating since April 2018, these programs have continued to grow and improve and have been successful in connecting hundreds of citizens to needed treatment and other social services. Program: HC ARC combats overdoses and overdose deaths by utilizing cross-sector planning and collaboration to operate 2 countywide programs: Quick Response Team (QRT) and Law Enforcement Assisted Diversion (LEAD). Implementation: The QRT and LEAD programs leverage partnerships with law enforcement, public health, addiction and mental health services, reentry services, and trained peer supporters. The QRT emphasizes triage, assessment, and connection to appropriate services for people with recent nonfatal drug overdoses and provides outreach and education in hot spot communities. LEAD provides diversion from the criminal justice system into long-term case management for nonviolent individuals with low-level offenses who also struggle with substance use disorder, mental health, homelessness, and/or poverty. Evaluation: QRT and LEAD team members routinely track and record client contacts and outcomes using a centralized electronic case management platform. Data are extracted and analyzed by the evaluation team to examine indices of program success and provide ongoing feedback to the QRT and LEAD teams. Discussion: HC ARC has implemented, tested, expanded, and now standardized its prearrest diversion programming. It has built a sustainable model to improve health and health equity for marginalized individuals whose needs intersect across health care, public health, community-based social services, and the criminal-legal system. Collectively, this work offers a guide for implementation and best practices for the following: detailed planning, policy, and procedure development; identification of key leaders and community partners; and methods to evaluate program operations to make data-driven decisions and real-time program adjustments.